Styrene Concentrations during Wheat Beer Production - Schwarz, Katrin; Methner, Frank-Jürgen (BrewingScience, 2011)
The screening of styrene concentrations during different stages of wheat beer production shows that in opposite to thermal processes like mashing and wort boiling the primary and secondary fermentation contribute most to the styrene content in final beers. Therefore, the enzymatic decarboxylation of cinnamic acid by brewers’ yeast is the predominant kind of reaction. Styrene concentrations in bottled beer were up to 25 ppb. In addition, the results of the screening were compared with the precursor concentration of cinnamic acid in the corresponding pitching wort. A linear correlation could not be found. Moreover, the influence of various manufacturing considerations like the kind of fermentation or the ratio of wheat grist load is shown. For example, the cinnamic acid content in wort decreases with an increasing amount of wheat malt.